CYANOBACTERIAL SECONDARY METABOLITES - SHWETA YADAV; R. P. SINHA; M. B. TYAGI; ASHOK KUMAR (International Journal of Pharma and Bio Sciences, 2011)
Cyanobacteria inhabit a range of diverse and extreme habitats and have potential to produce an elaborate array of secondary metabolites with unusual structures and potent bioactivity. This review summarizes several classes of cyanobacterial secondary metabolites some of which pose a threat to human or animal health in aquatic ecosystems because of their acute toxicity. This class includes hepatotoxins (microcystins and nodularins), neurotoxins (saxitoxin and anatoxins) and irritant toxins (lipopolysachharides). Another important class includes the phytohormones (IAAs, cytokinin and gibberillin-like compounds) and iron-chelators (schizokinen, anachelin and synechobactins) which besides exerting profound effect on the productivity of the ecosystem have also potential for use as medicine for treatment of persistent metal toxicity. Several cyclic peptides and depsipeptides such as cyanopeptolins, micropeptin and oscillaeptin which have been categorized as protease inhibitors make cyanobacteria unattractive as a food source to grazers and help in their survival. UV-screening compounds such as scytonemin and mycosporin-like amino acids (MAAs) produced by cyanobacteria inhabiting habitats exposed to intense solar radiation may find use in development of artificial sunscreens.